Different methods of termination of second trimester pregnancy at Women′s Health Hospital, Assiut University: efficacy and complications - Fathalla, Mohamed M.; Maghraby, Amr M.; AL-Hussaini, Tarek K.; Ismail, Alaa M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Termination of pregnancy in second trimester is one of the greatest challenges in modern obstetrics practice and is more risky than during first trimester. Now the main concern of the obstetrician is to provide the most effective, safest, and cost-effective regimen with least or no complications. Describe the different indications, technique and complications of different methods of TOP used at Women’s Health Hospital, Assiut University. Identify gap between current practice and guidelines and setting recommendations for filling gap to improve outcome Methods: Studying the different methods used for all cases with gestational age 13-24 weeks attending at Women′s Health Hospital, Assiut University from the 1st July 2015 to the 1st June 2016, for second trimester termination of pregnancy who are eligible for termination of pregnancy, with exclusion criteria including any case with scared uterus, multiple pregnancy and rupture of membranes. Results: Of the 146 patients, 55 patients received misoprostol alone, 13 cases used foley’s catheter alone, 67 cases received misoprostol in combination with foley’s catheter and hysterotomy done in 9 patients (4 after failed induction and the rest as primary procedure). In present work the most common complication recorded was retained placental parts, 39 patients (26,5%) followed by surgical evacuation. Uterine perforation occurred accidentally in 3 cases during evacuation followed by laparotomy and repair of perforation without hysterectomy. Infection recorded in 3 cases (1.7%). Sever haemorhage occurred in 4 cases where they needed hysterotomy. Conclusions: All methods used in the department showed efficacy. Misoprostol induction was associated with a shorter induction-abortion interval but was associated with higher risk of retained placenta. Foley’s catheter induction was more prolonged but it was associated with almost no complication. The most common complication was retained placenta except those who used Foley’s catheter as they had no retained placental parts.